The Second World War in the East - Willmott, H. P.; Keegan, John, 1934-2012. (London : Cassell, 1999)
This book is an illustrated account of the war between Japan and the Allies in the Far East and the Pacific.
The road to war -- The first milestone : success and victory : December 1941-April 1942 -- The second milestone : problems : May 1942-November 1943 -- The third milestone : the road to defeat, failure, and collapse : November 1943-October 1944 -- The last milestone : supremacy and victory : November 1944-August 1945.
Series statement on jacket.
Includes bibliographical references (pages 218-219) and index.
Keywords: 1939-1945; World War, 1939-1945 -- Campaigns -- Pacific Area; World War, 1939-1945 -- Campaigns -- Asia; Guerre mondiale, 1939-1945 -- Campagnes et batailles; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Asie; Military campaigns; World War, 1939-1945 -- Campaigns -- Pacific Area; World War, 1939-1945 -- Campaigns -- East Asia; Asia; Pacific Area